2018
DOI: 10.1007/s10900-018-0466-4
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Health Among Taxi Drivers in New York and Toronto

Abstract: Immigrant taxi drivers in metropolitan cities are exposed to experiences of discrimination and occupation-based health risks. Given the structural differences in health care systems in the United States and Canada, we investigated the differences in reports of discrimination, health conditions and concern about health conditions between taxi drivers in New York City and Toronto, Ontario. Participants were recruited for a taxi driver Needs Assessment Survey as part of a Taxi Network needs assessment project usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This not only has serious implications for work ability in people with chronic or persistent pain, but it exacerbates inequality in the workplace, and poses risks to career progression, as well as the physical and mental wellbeing of employees. A relationship between workplace discrimination and chronic pain has been identified previously [ 82 , 83 ]. In healthcare, the Institute of Medicine called for ‘a cultural transformation in the way in which pain is perceived, judged and treated’ [ 84 ] and this ethos should be transferable to the workplace setting; similarly, others advocate that stigmatisation of chronic pain, and its consequences, can only be addressed at a policy and practice (rather than individual cognitive) level [ 85 ].…”
Section: Discussionmentioning
confidence: 97%
“…This not only has serious implications for work ability in people with chronic or persistent pain, but it exacerbates inequality in the workplace, and poses risks to career progression, as well as the physical and mental wellbeing of employees. A relationship between workplace discrimination and chronic pain has been identified previously [ 82 , 83 ]. In healthcare, the Institute of Medicine called for ‘a cultural transformation in the way in which pain is perceived, judged and treated’ [ 84 ] and this ethos should be transferable to the workplace setting; similarly, others advocate that stigmatisation of chronic pain, and its consequences, can only be addressed at a policy and practice (rather than individual cognitive) level [ 85 ].…”
Section: Discussionmentioning
confidence: 97%
“…Prior research has indicated that taxi and FHV drivers are subject to a confluence of occupational factors that can negatively impact their interrelated financial, mental, and physical health. Drivers have reported that stress, discrimination, long hours, and low pay contribute to their poor health outcomes [ 1 , 4 , 16 ]. In metropolitan cities across the world, researchers have documented a range of health and wellness issues in taxi drivers, including fatigue [ 17 ], compromised immune function [ 18 ], chronic pain [ 19 ], diabetes [ 17 ], and increased cardiovascular disease and cancer risk [ 3 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Because of their sedentary occupation, poor diet, pollution exposure, discrimination, stressors, and ethnic backgrounds, drivers are at an elevated risk for cardiovascular disease (CVD), cancer, hypertension, obesity, and diabetes. 3 Most NYC drivers are independent contractors without workplace-sponsored health insurance. 1,3 Hence, many are uninsured (34% in a recent study) and lack a primary care provider (PCP).…”
Section: Introductionmentioning
confidence: 99%
“…3 Most NYC drivers are independent contractors without workplace-sponsored health insurance. 1,3 Hence, many are uninsured (34% in a recent study) and lack a primary care provider (PCP). 3 According to Andersen's widely acknowledged behavioral model of health services use, social context predisposes individuals to use services or not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation